1995
DOI: 10.1523/jneurosci.15-05-03689.1995
|View full text |Cite
|
Sign up to set email alerts
|

Visual topography in primate V2: multiple representation across functional stripes

Abstract: We thank John Maunsell for invaluable discussions and suggestions for data analysis; Geoffrey Ghose, Jonathan Horton, and Jon Kaas for helpful comments on the manuscript; and Lara Hinderstein and Carmela LoRusso for excellent technical support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
290
5

Year Published

1996
1996
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(336 citation statements)
references
References 56 publications
39
290
5
Order By: Relevance
“…Zeki and Shipp (1989) suggested that this segregation is not complete in V4, but rather some foci receive input from interstripes only, whereas other foci receive a mixed thin stripe and interstripe input. Recently, optical recording of intrinsic cortical signals has shown that V2 stripe compartments are functionally heterogeneous; interstripes and thick stripes contain orientation-selective domains (Malach et al, 1994), and thin stripes consist of separate clusters of cells activated by chromatic and luminance stimuli (Roe and Ts'o, 1995). Furthermore, the pattern of cytochrome oxidase activity is nonuniform within dense stripes such that individual stripes are best described as a series of beads on a string rather than as a uniform structure.…”
Section: Abstract: Functional Architecture; Temporal Lobe; Cortical mentioning
confidence: 99%
See 3 more Smart Citations
“…Zeki and Shipp (1989) suggested that this segregation is not complete in V4, but rather some foci receive input from interstripes only, whereas other foci receive a mixed thin stripe and interstripe input. Recently, optical recording of intrinsic cortical signals has shown that V2 stripe compartments are functionally heterogeneous; interstripes and thick stripes contain orientation-selective domains (Malach et al, 1994), and thin stripes consist of separate clusters of cells activated by chromatic and luminance stimuli (Roe and Ts'o, 1995). Furthermore, the pattern of cytochrome oxidase activity is nonuniform within dense stripes such that individual stripes are best described as a series of beads on a string rather than as a uniform structure.…”
Section: Abstract: Functional Architecture; Temporal Lobe; Cortical mentioning
confidence: 99%
“…5). Recently, Roe and Ts'o (1995) demonstrated a submodular organization within V2 thin stripes such that ϳ500 -1000 m wide zones are preferentially activated by isoluminant color or luminance stimuli, respectively. Because the cells within the cytochrome oxidase blobs of V1 are functionally heterogeneous (cf.…”
Section: Heterogeneity Within V2 Stripe Compartmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…These color patches were spatially associated with blobs in a somewhat loose sense and often enclosed interblob regions. Of their electrode penetrations that encountered color-selective cells, 29% were located outside blobs.In V2, color-selective cells and orientation-selective cells were found in all three types of CO compartments (7,(17)(18)(19)(20)(21)(22). In these studies, the percentage of color-selective cells in thin stripes ranged from 27% to 86%, whereas the percentage of orientation-selective cells ranged from 20% to 73%.…”
mentioning
confidence: 99%